NAVIGASI PILIHAN KONSUMEN: DAMPAK KEPUASAN PELANGGAN PADA PENGALAMAN MEREK, KUALITAS PRODUK, DAN MENTAL ACCOUNTING - Novitasari, Dwi; Mutmainnah, Lenita Alifatul; Wikaningtyas, Suci Utami; Kundala, Manendha Maganitri (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Noodles are one of the carbohydrate sources favored by many people around the world, including Indonesia. Lemonilo, as a pioneer of healthy instant noodles and a close competitor to Indomie, along with Mie Sedaap and Supermi, has not yet fully attracted consumers, resulting in low sales levels. The purpose of this study is to examine and analyze the influence of brand experience, product quality, and mental accounting on the purchase decisions of Lemonilo instant noodles, as well as the role of customer satisfaction as a moderator. This study uses a quantitative approach, employing a survey method with a questionnaire, resulting in a final sample of 105 respondents. Data were analyzed using Structural Equation Modeling (SEM). The results of the study indicate that brand experience positively affects customer satisfaction and purchase decisions. Product quality has a positive impact on purchase decisions but a negative effect on customer satisfaction. Additionally, findings show that mental accounting negatively affects purchase decisions while positively influencing satisfaction. Customer satisfaction negatively impacts purchase decisions. The results also demonstrate that customer satisfaction has a negative moderating effect on the relationships between brand experience, product quality, and mental accounting with purchase decisions. In this context, high customer satisfaction appears to diminish the positive impact of brand experience and product quality and strengthen the negative influence of mental accounting on purchase decisions. These findings provide important insights for marketing strategies, emphasizing the need for different approaches when customer satisfaction is already high.